PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS TERHADAP PENGUASAAN KOMPETENSI PENGETAHUAN IPS SISWA KELAS IV SD GUGUS II KUTA SELATAN TAHUN AJARAN 2017/2018 - Putu Dina Puspita (Indonesian Journal Of Educational Research and Review, 2018)
This study aimed to know the effect of cooperative learning type Pair Checks towards students’ mastery social science competence on the fourth grade students at SD Gugus II Kuta Selatan in academic year 2017/2018. The type of this research was quasi-experimental especially nonequivalent control group design. The population of this study was the fourth grade students at SD Gugus II Kuta Selatan in academic year 2017/2018 which consisted of 6 SD Negeri with 11 classes which consisted of 363 students. The sample of this study was done by using random sampling technique which was randomized to determine the experimental group and control group. In result, the fourth grade students of A class at SD No. 6 Benoa was the experimental group which consisted of 30 students and the fourth grade students of B class at SD No. 2 Tanjung Benoa was the control group which consisted of 34 students. Method of collecting data that was used in this study was multiple choice test. The data were analyzed by using descriptive and inferential statistical analysis. The result of data analysis showed that tcount = 5,594 and ttable = 2,000, at 5% significant level with dk = 62. This means that tcount = 5,594 > ttable = 2,000. The mean score mastery social science competence of students who were taught by cooperative learning type Pair Checks was higher, which was, 80.83 meanwhile the mean score of students who were taught by conventional learning was 70.62. In conclusion, it could be stated that cooperative learning type Pair Checks gave effect towards students’ social science competence on the fourth grade students at SD Gugus II Kuta Selatan in academic year 2017/2018.